Changes in dietary intake, immune function and performance monitors throughout a season in professional rugby league players - Tester, E.; Jones, B.; Duckworth, L.; Ispoglou, T. (International Journal of Sport Nutrition and Exercise Metabolism, 2017)
Throughout a rugby league (RL) season players are exposed to a high volume of competitive fixtures. Cumulative loads and inadequate nutrition may supress immune function, which would have negative consequences for health and performance. As no study has monitored immune function and dietary intake throughout a RL season, the aim of the study was to identify the pattern of dietary intake and critical time points where immune function and selected performance monitors are compromised. Following ethics approval, 20 male volunteer professional RL players (25.4±3.2 y, 98.2±8.4 kg) were monitored the day prior to a competitive fixture for 25 weeks of the season. Weekly changes in neuromus cular function (CMJ), wellbeing (5-point questionnaire), training loads (sRPE), salivary testosterone (sTest) and immunoglobulin A (sIgA) were recorded. Dietary intake (4-day food diary) was assessed at the start, middle and end of the season. Changes from the overall mean were inferred via Cohen`s d effect sizes using means and standard deviations which were calculated from a linear mixed model to account for missing data. Moderate increases in training load occurred in weeks 3, 5, 9, 10, 12 and 20 and a very large increase occurred in week 21. Moderate decreases in CMJ flight time occurred in week 14 and small decreases occurred in weeks 6, 7, 20, 22, 24, 25. For all wellbeing parameters small decreases occurred in weeks 7 and 17 with small increases in stress, soreness and fatigue also occurring in week 20. Mean sTest was 119.8±55.5 pg.ml-1 with small declines occurring in week 7, 10, 13, 20 and 22. Overall sIgA concentrations ranged from 1.03-1.18 ìg.min-1, but compared to the overall mean (1.12 ± 0.17 ìg.min-1) small decreases were observed in weeks 6, 9, 16, 21, 23, 24. Dietary intakes were consistent during the recording periods with mean energy intake ranging from 2811-3149 kcal.day-1. Carbohydrate, protein, and fat intakes ranged from 2.9-3.2 g.kg.BM-1, 2.0-2.1 g.kg.BM-1, and 1.1-1.4 g.kg.BM-1 respectively. The findings suggest that a consistent intake throughout a competitive season did not prevent reductions in immune function and selected performance monitors. Further research to develop appropriate periodised nutritional strategies to maintain immune function and support player health and performance is needed.